Supported catalyst, preparation method and application thereof, and method for preparing benzene by hydrodealkylation of alkylbenzene

By supporting chromium elements and rare earth elements on the composite pore molecular sieve support, adjusting the acid sites, and preparing high-active and highly selective catalysts, solving the problems of poor hydrodealkylation and high cost of aromatic hydrocarbons, achieving high efficiency Toluene conversion and benzene selectivity.

CN119237003APending Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310775671.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the problems of poor hydrodealkylation of aromatic hydrocarbons, high aromatic loss and high production costs are difficult to meet the needs of efficient benzene preparation.

Method used

The catalyst is prepared by acid treatment and calcination by chromium and rare earth elements, and the pore volume and specific surface area are adjusted to improve the activity and selectivity of the catalyst.

Benefits of technology

It achieves high conversion, high benzene selectivity and stability, reduces side reactions, improves the resistance to carbon deposits and stability of the catalyst, and is suitable for toluene hydrodealkylation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004309281500000111
    Figure BDA0004309281500000111
  • Figure BDA0004309281500000112
    Figure BDA0004309281500000112
  • Figure BDA0004309281500000113
    Figure BDA0004309281500000113
Patent Text Reader

Abstract

The invention relates to the field of catalysts, in particular to a supported catalyst, a preparation method and application thereof and a method for preparing benzene through hydrodealkylation of alkylbenzene. The catalyst comprises a composite pore molecular sieve carrier as well as a chromium element and a rare earth element which are loaded on the carrier, the pore volume of the catalyst is greater than 0.3 mL / g, and the specific surface area is less than 280 m < 2 > / g. The chromium element and the rare earth element are loaded on the composite pore molecular sieve carrier, so that the distribution of acidic sites of the composite pore molecular sieve carrier can be adjusted; the catalyst with the pore volume and the specific surface area within the range of the invention has high activity, selectivity and stability, for example, the catalyst has high hydrodealkylation activity and high benzene selectivity and stability when applied to hydrodealkylation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a supported catalyst, a preparation method and application thereof, and a method for preparing benzene by hydrogenating and dealkylating alkylbenzene. Background Art

[0002] Benzene is an important basic organic raw material with huge consumption. It has a rich industrial chain and scattered industrial bases. The main downstream products include ethylbenzene (41.0%), phenol (16%), caprolactam (16%), cyclohexane (12%), etc. In 2020, the world's pure benzene production capacity is about 69.45 million tons / a and the output is about 48.75 million tons / a. It is estimated that the world's pure benzene production capacity will reach 73.87 million tons / a in 2022, and the demand for pure benzene will reach 52.78 million tons / a. In 2021, the domestic benzene (including petroleum benzene and hydrogenated benzene, the same below) production capacity is 26.125 million tons, China's demand is 20.94 tons, the output is 18.05 million tons, and the gap is 2.89 million tons. The gap will expand to 5.72 million tons in 2025, and the gap will expand to 6.24 million tons by 2050. Overall, the absolute value of the benzene supply gap continues to expand. From 2022 to 2025, the downstream styrene and phenol ketone production capacity expansion rate will be higher than that of benzene. In the long run, the benzene gap will continue to expand, and the import dependence of the benzene market is expected to remain above 20%. In the long run from 2022 to 2050, the supply of China's benzene market will still be less than the demand, and the distribution of resources will still be uneven. The East China market will still be the main consumer market. In addition, in recent years, the environmental protection requirements of various regions have been continuously upgraded, making the transportation of benzene more difficult and expensive, and the shortage of local benzene resources has increased. The above market environment has made efficient benzene production technology continue to be favored by enterprises. On the one hand, it can meet the demand of the benzene market, and on the other hand, it can find new conversion technologies for squeezing out inferior aromatics for oil product upgrading.

[0003] At present, the chemical processes that directly produce benzene mainly include: catalytic reforming, ethylene cracking, and coal chemical coking. Among them, in addition to benzene, the catalytic reforming and ethylene cracking processes will also produce many other alkylbenzenes, and the benzene output is limited. The coal chemical industry has high carbon emissions, and the call for "carbon neutrality" is becoming increasingly strong. In the future, the benzene output of the coking industry may be compressed. In addition, toluene disproportionation technology is currently the most widely used technology for increasing benzene production, but toluene disproportionation technology can theoretically only achieve 2 moles of toluene to increase the production of 1 mole of benzene and 1 mole of xylene. The raw materials are limited and the efficiency of increasing benzene production cannot be maximized. The existing heavy aromatics lightening technology is only for C2 + The side chain removal efficiency is high, but the methyl group cannot be removed efficiently. The product is mainly xylene, and the benzene output is extremely limited. Therefore, it is urgent to seek other efficient benzene production technologies.

[0004] The technology of benzene production by dealkylation of aromatics is to effectively remove the side chain alkyl groups including methyl and above through the side chain dealkylation technology, and efficiently convert aromatics into benzene. Theoretically, 1 mole of aromatics can produce 1 mole of benzene, which is the most efficient benzene production technology at present. Aromatic dealkylation includes hydrodealkylation, non-hydrodealkylation, and steam reforming dealkylation. The hydrodealkylation technology is currently used in industry. Among them, the catalytic hydrodealkylation technology has a lower apparent activation energy of the reaction due to the presence of the catalyst, so that at the same reaction temperature, the reaction rate of the catalytic hydrodealkylation reaction is faster than that of the thermal cracking hydrodealkylation reaction. Under the same conversion rate conditions, its reaction temperature is low and the selectivity of benzene is high. The two processes of thermal cracking hydrodealkylation and catalytic hydrodealkylation have their own characteristics. The reaction temperature of catalytic hydrodealkylation is low, which mainly involves the dealkylation of alkyl aromatics and the hydrocracking reaction of non-aromatics. The saturated hydrogenation and cracking reaction inhibition rate of aromatic rings is high, which makes the hydrogen consumption of this technology relatively low and the selectivity of benzene can reach more than 98 mol% of the theoretical value. Thermal cracking hydrodealkylation technology has a high reaction temperature and the reaction process is a free radical mechanism. On the one hand, the high reaction temperature leads to an increase in side reactions such as cracking and polymerization. On the other hand, the free radical reaction process easily generates biphenyl, which makes the benzene selectivity about 3% lower than that of catalytic hydrodealkylation technology. The hydrogen consumption is also relatively high. However, this technology does not require the use of a catalyst, making the reaction process relatively simple, and the non-aromatic hydrocarbons in the raw materials can reach 30%.

[0005] Carry out research on the technology of catalytic hydrogenation and dealkylation of aromatics to produce benzene, and flexibly adopt C7 + Aromatic hydrocarbons are used as raw materials and hydrogenated fixed bed reactors are used to efficiently remove side chain alkyl groups including methyl groups by means of the hydrogenation dealkylation reaction of aromatic ring side chains, and alkylbenzenes are converted into benzene. The aim is to develop a new benzene production technology with a wide source of raw materials, high benzene production efficiency, and low equipment investment to meet the demand for increased benzene production. Therefore, the development of high-conversion and high-stability alkylbenzene hydrogenation dealkylation benzene production catalysts has a wide market demand and good application prospects.

[0006] CN 1227193 C [Petrochemical Research Institute (Beijing), 2005.11.16] discloses a catalyst for lightening heavy aromatic hydrocarbons, comprising 0.01-2.0 wt% of Group VIII metal and a composite carrier, wherein the composite carrier comprises 30-70 wt% of ZSM-5 zeolite, 5-30 wt% of β zeolite and 10-65 wt% of alumina. The catalyst is used for lightening heavy aromatic hydrocarbons, can improve the conversion rate of C9+ aromatic hydrocarbons and the yield of benzene and xylene, and reduce carbon deposition.

[0007] CN 1050777 C [Tianjin University, 2000.03.29] discloses a novel Cr2O3-RE / Al2O3 catalyst for catalytic dealkylation of C9-10 alkyl aromatics to produce xylene, toluene and benzene, wherein the carrier Al2O3 is treated with rare earth, and the catalyst has a stable structure and a selectivity for triphenylene greater than 95% (conversion rate 58%). The catalyst of the present invention is that rare earth La2O3 is loaded on the surface of γ-Al2O3, and the acidity of γ-Al2O3 is adjusted through high temperature treatment, and the Cr2O3 grains are uniformly distributed on the surface of γ-Al2O3. The catalyst of the present invention is that rare earth La2O3 is loaded on the surface of γ-Al2O3, and the acidity of γ-Al2O3 is adjusted through high temperature treatment, and the Cr2O3 grains are uniformly distributed on the surface of γ-Al2O3. The catalyst can also be used in the process of catalytic dealkylation of toluene to produce benzene.

[0008] CN 101444745 A [Jinzhou Petrochemical Fine Chemical Co., Ltd., 2009.06.09] discloses a method for preparing a catalyst for steam dealkylation of heavy aromatic hydrocarbons. The catalyst is prepared by impregnating a nitrate solution of a rare earth metal or an alkaline earth metal into a silicon-aluminum molecular sieve, and then ion-exchanging the catalyst in a water bath, repeatedly washing the catalyst until the catalyst is neutral, drying the catalyst, and calcining the catalyst. The catalyst is suitable for steam dealkylation reaction, has low preparation cost, good stability, long service life, and is easy to regenerate. The catalyst can be used to produce high-purity trimethylol in a dealkylation reaction, and has a high conversion rate and a purity of more than 90%.

[0009] CN111068769A [Hebei University of Technology, 2020.04.28] provides a catalyst for catalytic hydrogenation and demethylation of xylenol, and its preparation method and application. The catalyst comprises a composite carrier and an acidic active component; the composite carrier is a composite of a modified HY molecular sieve and an Al-MCM-41 molecular sieve, and the modified HY molecular sieve is coated with an Al-MCM-41 molecular sieve to form a HY / MCM-41 coated composite molecular sieve; the modified HY molecular sieve is a HY molecular sieve loaded with an acidic active component; the acidic active component is SO4 2- / TiO2; wherein the mass of the modified HY molecular sieve is 20-80% of the mass of the composite carrier; SO4 2- The mass of TiO2 is 3-8% of the mass of HY molecular sieve. The catalyst provided by the invention has suitable acidity and micro / mesoporous structure, and exhibits high 3,4-dimethylphenol conversion rate, phenol and cresol selectivity and good stability.

[0010] From the above review, it can be seen that although the preparation method of aromatic catalytic dealkylation molecular sieve is relatively mature, there is almost no catalyst that can solve the problems of poor activity and high aromatic loss in aromatic hydrodealkylation. At the same time, the additives and metals used in the molecular sieve synthesis process are expensive, and the production cost is high. Therefore, the development of high conversion and high stability toluene hydrodealkylation catalysts for benzene production has a wide market demand and good application prospects. Summary of the invention

[0011] The purpose of the present invention is to overcome the problems of poor aromatics hydrodealkylation activity, high aromatic loss and high production cost in the prior art, and to provide a supported catalyst, a preparation method and application thereof, and a method for preparing benzene by hydrodealkylation of alkylbenzene. The catalyst has the advantages of high activity, high benzene selectivity and high stability.

[0012] In order to achieve the above object, the present invention provides a supported catalyst in the first aspect, which comprises a composite pore molecular sieve carrier and chromium and rare earth elements supported on the carrier; the pore volume of the catalyst is greater than 0.3 mL / g, and the specific surface area is less than 280 m 2 / g.

[0013] The second aspect of the present invention provides a method for preparing the catalyst, the method comprising:

[0014] (1) first loading a rare earth metal source onto an acid-treated composite pore molecular sieve carrier, performing a first drying and a first calcination to obtain a catalyst intermediate;

[0015] (2) A chromium source is loaded onto the catalyst intermediate for a second time, followed by a second drying and a second calcination.

[0016] The third aspect of the present invention provides an application of the catalyst in preparing benzene by hydrogenation and dealkylation of alkylbenzene.

[0017] A fourth aspect of the present invention provides a method for preparing benzene by hydrogenating and dealkylating alkylbenzene. The method comprises: contacting a hydrogen raw material and an alkylbenzene raw material for reaction in the presence of the catalyst.

[0018] Through the above technical solution, the present invention has the following advantages:

[0019] The present invention loads chromium and rare earth elements on a composite pore molecular sieve carrier, and can adjust the distribution of the acid sites of the composite pore molecular sieve carrier, so that the catalyst having a pore volume and a specific surface area within the scope of the present invention has high activity, selectivity and stability. For example, when applied to hydrodealkylation, the catalyst has high hydrodealkylation activity, high benzene selectivity and stability.

[0020] In specific applications, the catalyst of the present invention is demonstratively used in the toluene hydrodealkylation reaction, with high toluene conversion rate, high benzene selectivity, few side reactions, and unexpectedly found that the aromatic ring loss rate of toluene as a raw material is low, the aromatic hydrocarbon yield can reach more than 99.89%, and the catalyst has the characteristics of resistance to carbon deposition and high stability. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] In the present invention, the composite pore molecular sieve refers to: a mesoporous structure is introduced into the synthesis system of a traditional microporous molecular sieve to form a composite pore molecular sieve, which can make the molecular sieve have high diffusion, anti-carbon deposition and anti-clogging properties.

[0023] The present invention provides a supported catalyst, which comprises a composite pore molecular sieve carrier and chromium and rare earth elements supported on the carrier; the pore volume of the catalyst is greater than 0.3 mL / g, and the specific surface area is less than 280 m 2 / g.

[0024] The present invention loads chromium and rare earth elements on a composite pore molecular sieve carrier, and can adjust the distribution of acid sites of the composite pore molecular sieve carrier, so that the catalyst having pore volume and specific surface area within the scope of the present invention has high activity, selectivity and stability.

[0025] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular restriction on the volume ratio of the micropores and mesopores of the composite molecular sieve. According to a preferred embodiment of the present invention, the volume ratio of the micropores and mesopores of the composite molecular sieve is 2.8-8.5, preferably 3.5-6.0, for example, the volume ratio of the micropores and mesopores of the composite molecular sieve can be 2.8, 3.0, 3.5, 4.0, 5.0, 5.5, 6.0, 7.0, 8.0, 8.5. By adopting the aforementioned preferred scheme, it is beneficial to adjust the pore size distribution of the molecular sieve carrier, improve the diffusion efficiency of the raw material molecules, and promote the raw material molecules to fully contact with the active reactions inside and outside the pores, thereby further improving the activity, selectivity and stability of the catalyst.

[0026] According to a preferred embodiment of the present invention, the mesopore diameter of the composite molecular sieve is 5-35 nm, preferably 8-18 nm. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0027] According to a preferred embodiment of the present invention, the pore volume of the catalyst is 0.40-1.2 mL / g, preferably 0.65-0.95 mL / g.

[0028] According to a preferred embodiment of the present invention, the specific surface area of ​​the catalyst is 100-265m 2 / g, preferably 125-205m 2 / g.

[0029] According to a preferred embodiment of the present invention, the average pore size of the catalyst is 4.5-16nm, preferably 6.0-12.5nm. In the present invention, there are many optional types of composite pore molecular sieves. According to a preferred embodiment of the present invention, the type of composite pore molecular sieve is selected from at least one of MCM-22 molecular sieve, mercerized molecular sieve, ZSM-5 molecular sieve, β molecular sieve, and Y molecular sieve, preferably at least one of MCM-22 molecular sieve, mercerized molecular sieve, and ZSM-5 molecular sieve.

[0030] In the present invention, there are many optional types of composite pore molecular sieves. According to a preferred embodiment of the present invention, the composite pore molecular sieve is a mixed molecular sieve with a mass ratio of MCM-22 molecular sieve to ZSM-5 molecular sieve of 80-60:20-40. By adopting the above preferred scheme, it is beneficial to adjust the distribution of acid sites of the catalyst carrier, provide conditions for the loading of metal active components, and at the same time, it is beneficial to improve the activity, selectivity and stability of the catalyst.

[0031] In the present invention, the rare earth element can be a conventional choice in the art. According to a preferred embodiment of the present invention, the rare earth element is a rare earth oxide, preferably the rare earth oxide is selected from at least one of lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide and samarium oxide, more preferably at least one of lanthanum oxide, cerium oxide and praseodymium oxide.

[0032] According to a preferred embodiment of the present invention, the rare earth oxide is a mixture of lanthanum oxide, cerium oxide and praseodymium oxide, and the molar ratio of lanthanum oxide, cerium oxide and praseodymium oxide in the mixture is preferably 0.90-0.50: 0.05-0.30: 0.05-0.20. By adopting the above preferred embodiment, the alkaline rare earth oxide can adjust the acidity of the carrier molecular sieve on the one hand, and on the other hand, it can also promote the chromium element to be more evenly distributed on the surface of the molecular sieve.

[0033] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of each component in the catalyst. According to a preferred embodiment of the present invention, the weight ratio of the composite pore molecular sieve carrier, chromium in oxide and rare earth in oxide in the catalyst is 1:0.03-0.10:0.05-0.15; preferably 1:0.05-0.08:0.09-0.13. By adopting the above preferred scheme, the activity, selectivity and stability of the catalyst can be further improved.

[0034] In the present invention, there is no special requirement for the preparation method of the catalyst, as long as the catalyst having the aforementioned characteristics of the present invention can be obtained. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the catalyst, which comprises:

[0035] (1) first loading a rare earth metal source onto an acid-treated composite pore molecular sieve carrier, performing a first drying and a first calcination to obtain a catalyst intermediate;

[0036] (2) A chromium source is loaded onto the catalyst intermediate for a second time, followed by a second drying and a second calcination.

[0037] The catalyst prepared by the above method can further improve the activity, selectivity and stability of the catalyst.

[0038] In the present invention, there is no particular limitation on the concentration of the acid used in the acid treatment in step a. According to a preferred embodiment of the present invention, the concentration of the acid used in the acid treatment is 0.01-0.2 mol / L, preferably 0.05-0.15 mol / L.

[0039] In the present invention, the conditions for the acid treatment may be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions for the acid treatment include: a temperature of 45-100°C, preferably 60-95°C.

[0040] According to a preferred embodiment of the present invention, the conditions for the acid treatment include: a time of 4-12 hours, preferably 6-8 hours.

[0041] According to a preferred embodiment of the present invention, the conditions for the acid treatment include: a liquid-to-solid ratio of 4.5-15, preferably 6-11.

[0042] According to a preferred embodiment of the present invention, the acid treatment uses an acid selected from inorganic acids and / or organic acids, preferably at least one selected from oxalic acid, citric acid, acetic acid and hydrochloric acid, more preferably at least one selected from oxalic acid, citric acid and acetic acid.

[0043] By adopting the preferred embodiment of the above-mentioned acid treatment, on the one hand, the amorphous silicon aluminum contained in the molecular sieve can be cleaned out to improve the catalytic efficiency of the molecular sieve, and on the other hand, aluminum can be removed to a certain extent, the silicon-aluminum ratio of the molecular sieve can be increased, and the acidity of the molecular sieve can be reduced. This has a synergistic effect with the reduction of the acidity of the molecular sieve by rare earth metals, further improving the activity, selectivity and stability of the prepared catalyst.

[0044] In the present invention, the chromium source has a wide range of selectable sources. According to a preferred embodiment of the present invention, the chromium source is selected from at least one of chromium nitrate, chromium sulfate, chromium chloride and potassium alum, preferably at least one of chromium nitrate, chromium sulfate and chromium chloride. By adopting the above preferred embodiment, the activity, selectivity and stability of the prepared catalyst can be further improved.

[0045] In the present invention, the optional range of the rare earth metal source is relatively wide. According to a preferred embodiment of the present invention, the rare earth metal source is selected from at least one of lanthanum nitrate, cerium nitrate, praseodymium nitrate, neodymium nitrate and samarium nitrate, preferably at least one of lanthanum nitrate, cerium nitrate and praseodymium nitrate.

[0046] In the present invention, the first loading and the second loading can be carried out in a manner conventionally selected in the art, such as impregnation.

[0047] According to a preferred embodiment of the present invention, the conditions of the first load include: a temperature of 50-150°C, preferably 80-120°C.

[0048] The time of the first load depends on the load temperature. According to a preferred embodiment of the present invention, the conditions of the first load include: the time is 4-12 hours, preferably 6-8 hours.

[0049] According to a preferred embodiment of the present invention, the first drying conditions include: a temperature of 70-150°C, preferably 90-120°C.

[0050] The time of the first drying depends on the drying temperature. According to a preferred embodiment of the present invention, the conditions of the first drying include: a time of 5-10 hours, preferably 6-9 hours.

[0051] According to a preferred embodiment of the present invention, the conditions for the first calcination include: a temperature of 400-650°C, preferably 450-550°C.

[0052] The time of the first roasting depends on the roasting temperature. According to a preferred embodiment of the present invention, the conditions of the first roasting include: the time is 2-8 hours, preferably 4-6 hours.

[0053] According to a preferred embodiment of the present invention, the conditions of the second load include: a temperature of 50-150°C, preferably 80-120°C.

[0054] The time of the second load depends on the load temperature. According to a preferred embodiment of the present invention, the conditions of the second load include: the time is 6-15 hours, preferably 8-12 hours.

[0055] According to a preferred embodiment of the present invention, the second drying conditions include: a temperature of 70-150°C, preferably 90-120°C.

[0056] The second drying time depends on the drying temperature. According to a preferred embodiment of the present invention, the second drying conditions include: the time is 5-10 hours, preferably 6-9 hours.

[0057] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a temperature of 400-600°C, preferably 450-550°C.

[0058] The time of the second roasting depends on the roasting temperature. According to a preferred embodiment of the present invention, the conditions of the second roasting include: the time is 2-8 hours, preferably 2-6 hours.

[0059] The present invention provides an application of the catalyst in preparing benzene by hydrogenating and dealkylating alkylbenzene. Preferably, the alkyl group in the alkylbenzene is a C1-C5 alkyl group, and more preferably, the alkylbenzene is toluene.

[0060] The invention provides a method for preparing benzene by hydrogenating and dealkylating alkylbenzene. The method comprises: contacting and reacting a hydrogen raw material and an alkylbenzene raw material in the presence of the catalyst.

[0061] The catalyst of the present invention is used in the toluene hydrodealkylation reaction, and the toluene conversion rate is high, the benzene selectivity is high, the side reaction is less, and it is unexpectedly found that the aromatic ring loss rate of toluene as a raw material is low, the aromatic hydrocarbon yield can reach more than 99.89%, and the catalyst has the characteristics of anti-carbon deposition and high stability.

[0062] In the present invention, the conditions for the contact reaction can be selected in a wide range. According to a preferred embodiment of the present invention, the conditions for the contact reaction include: a temperature of 400-600°C, preferably 420-550°C.

[0063] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: a pressure of 0.1-5 MPa, preferably 0.5-3.5 MPa.

[0064] According to a preferred embodiment of the present invention, the contact reaction conditions include: the mass space velocity of alkylbenzene is 1-10h -1, preferably 2.0-5.0h -1 .

[0065] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: a hydrogen-to-oil ratio of 500-1500, preferably 800-1200.

[0066] According to a preferred embodiment of the present invention, the alkyl group in the alkylbenzene is a C1-C5 alkyl group, and more preferably the alkylbenzene is toluene.

[0067] The present invention will be described in detail below through examples.

[0068] In the following examples, the specific surface area and pore volume (pore volume) of the catalyst were determined by low-temperature nitrogen adsorption method. The specific test method is as follows: Nitrogen adsorption / desorption characterization was performed using the American Micromeritics ASAP 2420 automatic adsorption instrument. The sample was degassed at 350°C and 1.33Pa for 4h and then tested at -196°C with nitrogen as the adsorbent. The specific surface area was calculated by the BET method, the micropore specific surface area and the external specific surface area were calculated by the t-plot method, the total pore volume was calculated by the amount of N2 adsorbed when p / p0=0.99, and the micropore volume and mesopore volume were calculated by the t-plot and BJH methods, respectively.

[0069] The average pore size is obtained by dividing the corresponding pore volume by the corresponding specific surface area.

[0070] The calculation formulas for toluene conversion, benzene selectivity, and aromatic ring loss rate are as follows:

[0071]

[0072]

[0073]

[0074] Stability evaluation: Catalyst stability refers to the ability of a catalyst to maintain activity, selectivity, anti-toxicity, thermal stability and structure during the catalytic reaction. In the present invention, catalyst stability refers to the time during which the toluene conversion rate in the reaction drops to 90% of the initial conversion rate.

[0075] Unless otherwise specified, all raw materials were commercially available.

[0076] Example 1

[0077] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 5.8 and a mesopore diameter of 15 nm; select oxalic acid to prepare an acid solution with a concentration of 0.1 mol / L, and perform acid treatment at a liquid-to-solid ratio of 8, the acid treatment temperature is 85°C, and the acid treatment time is 7h; after the acid treatment, filter and dry, the drying temperature and time are 120°C and 8h respectively;

[0078] b. Prepare a lanthanum nitrate solution, wherein the lanthanum nitrate is 12% of the mass of the acid-treated molecular sieve carrier in terms of La2O3; impregnate the acid-treated molecular sieve carrier in the lanthanum nitrate solution by equal volume impregnation at a temperature of 90°C for 8 hours, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing a rare earth metal;

[0079] c. Prepare a chromium nitrate active metal solution, wherein the chromium nitrate is 8% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in the chromium nitrate solution for 10 hours by equal volume impregnation at a temperature of 90°C, dry at 100°C for 8 hours, and calcine at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0080] Example 2

[0081] a. Select a mordenite molecular sieve with a volume ratio of micropores to mesopores of 4.4 and a mesopore diameter of 9 nm; select oxalic acid to prepare an acid solution with a concentration of 0.06 mol / L, and perform acid treatment at a liquid-to-solid ratio of 10, wherein the acid treatment temperature is 85°C and the acid treatment time is 7h; after the acid treatment, the mixture is filtered and dried, and the drying temperature and time are 120°C and 8h respectively;

[0082] b. Prepare a cerium nitrate solution, wherein the cerium nitrate is 10% of the mass of the acid-treated molecular sieve carrier in terms of CeO2; impregnate the acid-treated molecular sieve carrier in the lanthanum nitrate solution by equal volume impregnation at a temperature of 90°C for 6 hours, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing a rare earth metal;

[0083] c. Prepare a chromium-containing active metal solution of chromium sulfate, wherein the chromium sulfate is 6% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in a chromium nitrate solution for 12 hours by equal volume impregnation at a temperature of 100°C, dry at 90°C for 9 hours, and calcine at 540°C for 3 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0084] Example 3

[0085] a. Select a ZSM-5 molecular sieve with a volume ratio of micropores to mesopores of 3.5 and a mesopore diameter of 18 nm; select citric acid to prepare an acid solution with a concentration of 0.06 mol / L, and perform acid treatment at a liquid-to-solid ratio of 1:1, wherein the acid treatment temperature is 60°C and the acid treatment time is 8h; after the acid treatment, the mixture is filtered and dried, and the drying temperature and time are 120°C and 8h respectively;

[0086] b. Prepare a mixed solution of lanthanum nitrate and cerium nitrate, wherein the lanthanum nitrate is 7% of the mass of the acid-treated molecular sieve carrier in terms of La2O3, and the cerium nitrate is 7% of the mass of the acid-treated molecular sieve carrier in terms of CeO2; impregnate the acid-treated molecular sieve carrier in the mixed solution of lanthanum nitrate and cerium nitrate for 8 hours by equal volume impregnation at a temperature of 90°C, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing rare earth metals;

[0087] c. Prepare a chromium chloride active metal solution, wherein the chromium nitrate is 8% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in the chromium nitrate solution for 10 hours by equal volume impregnation at a temperature of 85°C, dry at 100°C for 8 hours, and calcine at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0088] Example 4

[0089] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 3.6 and a mesopore diameter of 18 nm; select acetic acid to prepare an acid solution with a concentration of 0.15 mol / L, and perform acid treatment at a ratio of liquid to solid of 10, wherein the acid treatment temperature is 95°C and the acid treatment time is 8h; after the acid treatment, the mixture is filtered and dried, and the drying temperature and time are 120°C and 8h respectively;

[0090] b. Prepare praseodymium nitrate solution, in which Pr6O 11 The praseodymium nitrate is 12% of the mass of the acid-treated molecular sieve carrier; the acid-treated molecular sieve carrier is impregnated in the praseodymium nitrate solution for 8 hours by equal volume impregnation at a temperature of 90° C., dried at 115° C. for 6 hours, and calcined at 550° C. for 8 hours to obtain an intermediate containing a rare earth metal;

[0091] c. Prepare a chromium nitrate active metal solution, wherein the chromium nitrate is 4% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in the chromium nitrate solution for 12 hours by equal volume impregnation at a temperature of 110°C, dry at 100°C for 8 hours, and calcine at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0092] Example 5

[0093] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 5.1 and a mesopore diameter of 10 nm; select oxalic acid to prepare an acid solution with a concentration of 0.08 mol / L, and perform acid treatment at a liquid-to-solid ratio of 8, wherein the acid treatment temperature is 85°C and the acid treatment time is 7h; after the acid treatment, filter and dry, and the drying temperature and time are 120°C and 8h respectively;

[0094] b. Prepare a lanthanum nitrate solution, wherein the lanthanum nitrate is 10% of the mass of the acid-treated molecular sieve carrier in terms of La2O3; impregnate the acid-treated molecular sieve carrier in the lanthanum nitrate solution by equal volume impregnation at a temperature of 93°C for 8 hours, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing a rare earth metal;

[0095] c. Prepare a mixed solution of chromium nitrate and chromium chloride containing active chromium metal, wherein, in terms of Cr2O3, chromium nitrate is 4% of the mass of the acid-treated molecular sieve support, and chromium chloride is 4% of the mass of the acid-treated molecular sieve support; by equal volume impregnation, the impregnation temperature is 90°C, the intermediate obtained in b is impregnated in the mixed solution of chromium nitrate and chromium chloride for 10 hours, dried at 100°C for 8 hours, and calcined at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0096] Example 6

[0097] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 3.0 and a mesopore diameter of 6 nm; select hydrochloric acid to prepare an acid solution with a concentration of 0.10 mol / L, and perform acid treatment at a liquid-to-solid ratio of 8, wherein the acid treatment temperature is 100°C and the acid treatment time is 5h; after the acid treatment, filter and dry, and the drying temperature and time are 120°C and 8h respectively;

[0098] b. Prepare a lanthanum nitrate solution, wherein the lanthanum nitrate is 12% of the mass of the acid-treated molecular sieve carrier in terms of La2O3; impregnate the acid-treated molecular sieve carrier in the lanthanum nitrate solution by equal volume impregnation at a temperature of 90°C for 8 hours, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing a rare earth metal;

[0099] c. Prepare a chromium nitrate active metal solution, wherein the chromium nitrate is 8% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in the chromium nitrate solution for 10 hours by equal volume impregnation at a temperature of 90°C, dry at 100°C for 8 hours, and calcine at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0100] Example 7

[0101] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 5.8 and a mesopore diameter of 15 nm; select oxalic acid to prepare an acid solution with a concentration of 0.1 mol / L, and perform acid treatment at a liquid-to-solid ratio of 8, wherein the acid treatment temperature is 85°C and the acid treatment time is 7h; after the acid treatment, filter and dry, and the drying temperature and time are 120°C and 8h respectively;

[0102] b. Prepare a samarium nitrate solution, wherein the samarium nitrate is 12% of the mass of the acid-treated molecular sieve carrier in terms of Sm2O3; impregnate the acid-treated molecular sieve carrier in the samarium nitrate solution for 5 hours by equal volume impregnation at a temperature of 60°C, dry at 80°C for 5 hours, and calcine at 600°C for 8 hours to obtain an intermediate containing a rare earth metal;

[0103] c. Prepare a chromium nitrate active metal solution, wherein the chromium nitrate is 8% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; impregnate the intermediate obtained in b in the chromium nitrate solution for 10 hours by equal volume impregnation at a temperature of 90°C, dry at 100°C for 8 hours, and calcine at 550°C for 4 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0104] Example 8

[0105] a. Select MCM-22 molecular sieve with a volume ratio of micropores to mesopores of 5.8 and a mesopore diameter of 15 nm; select oxalic acid to prepare an acid solution with a concentration of 0.1 mol / L, and perform acid treatment at a liquid-to-solid ratio of 8, wherein the acid treatment temperature is 85°C and the acid treatment time is 7h; after the acid treatment, filter and dry, and the drying temperature and time are 120°C and 8h respectively;

[0106] b. Prepare a lanthanum nitrate solution, wherein the lanthanum nitrate is 12% of the mass of the acid-treated molecular sieve carrier in terms of La2O3; impregnate the acid-treated molecular sieve carrier in the lanthanum nitrate solution by equal volume impregnation at a temperature of 90°C for 8 hours, dry at 120°C for 6 hours, and calcine at 550°C for 6 hours to obtain an intermediate containing a rare earth metal;

[0107] c. Prepare a chromium-containing active metal solution of potassium alum, wherein potassium alum is 8% of the mass of the acid-treated molecular sieve carrier in terms of Cr2O3; immerse the intermediate obtained in b in the potassium alum solution for 14 hours by equal volume impregnation at a temperature of 150°C, dry at 80°C for 10 hours, and calcine at 600°C for 7 hours to obtain a finished catalyst containing metallic Cr. The physicochemical properties of the finished catalyst are shown in Table 1.

[0108] Example 9

[0109] Referring to Example 1, the mixed impregnation solution of lanthanum nitrate, cerium nitrate and praseodymium nitrate prepared in step b was changed, and the molar ratio of lanthanum oxide, cerium oxide and praseodymium oxide in the mixed impregnation solution was 0.70:0.20:0.10, and other conditions remained unchanged. The physicochemical properties of the finished catalyst are shown in Table 1.

[0110] Example 10

[0111] Referring to Example 1, the concentration of oxalic acid in step a was changed to 0.25 mol / L; the liquid-to-solid ratio was 4, and other conditions remained unchanged; the physicochemical properties of the finished catalyst are shown in Table 1.

[0112] Embodiment 11

[0113] Referring to Example 1, the MCM-22 molecular sieve in step a was replaced with a mixed molecular sieve of MCM-22 molecular sieve and ZSM-5 molecular sieve in a mass ratio of 70:30, and other conditions remained unchanged; the physicochemical properties of the finished catalyst are shown in Table 1.

[0114] Comparative Example 1

[0115] Refer to Example 1, except that the acid treatment step in operation a of Example 1 is not performed, and the other steps are performed according to Example 1. The physicochemical properties of the finished catalyst are shown in Table 1.

[0116] Comparative Example 2

[0117] Referring to Example 1, except that the equal volume impregnation step of rare earth metal solution in operation b of Example 1 was not performed, the other steps were performed in accordance with Example 1. The physicochemical properties of the finished catalyst are shown in Table 1.

[0118] Comparative Example 3

[0119] Referring to Example 1, except that the equal volume impregnation step of the chromium solution in operation C of Example 1 was not performed, the other steps were performed in accordance with Example 1. The physicochemical properties of the finished catalyst are shown in Table 1.

[0120] Comparative Example 4

[0121] Referring to Example 1, the difference is that after step a, step c is performed first, and then step b is performed, and the rest is the same as in Example 1 to obtain a finished catalyst. The physicochemical properties of the finished catalyst are shown in Table 1.

[0122] Comparative Example 5

[0123] Referring to Example 1, the composite pore molecular sieve MCM-22 molecular sieve in step a was replaced with a microporous molecular sieve MCM-22 molecular sieve with a pore size of 0.55 nm, and other conditions remained unchanged. The physicochemical properties of the finished catalyst are shown in Table 1.

[0124] Comparative Example 6

[0125] Referring to Example 1, the active metal Cr2O3 in step c was replaced with an equal mass of MoO3, and other conditions remained unchanged. The physicochemical properties of the finished catalyst are shown in Table 1.

[0126] Table 1

[0127]

[0128]

[0129] Example 12

[0130] 5.0 g of the finished catalysts prepared in Examples 1-11 and Comparative Tests 1-6 were respectively taken and loaded into a micro-insulated fixed bed reactor with an inner diameter of 1.5 cm. Glass beads were filled on the upper and lower sides of the reaction bed, and then hydrogen was introduced to ensure that the gas flow evenly flowed through the catalyst bed; the temperature was raised to 500° C. for 120 minutes, and after the temperature was kept constant for 2 hours, toluene raw material was introduced with a metering pump to maintain the mass space velocity of the organic reaction raw material at 2.0 h -1 , the reaction pressure was 3.0 MPa, and the hydrogen-to-oil ratio was 800. The toluene conversion rate, benzene selectivity, aromatic ring loss rate and stability of the reaction were finally calculated by measuring the oil phase, water phase and reaction tail gas in the catalytic reaction effluent and performing gas chromatography analysis. The specific results are shown in Table 2.

[0131] Comparative Example 7

[0132] Referring to Example 12, the raw material toluene was replaced with heavy aromatic hydrocarbon 1,2,4-trimethylbenzene, and the catalyst prepared in Example 11 and the catalyst of Comparative Examples 1-6 were used for catalytic reaction, and other conditions remained unchanged. The toluene conversion rate, benzene selectivity, aromatic ring loss rate and stability of the reaction were finally calculated by measuring the oil phase and water phase in the catalytic reaction effluent and performing gas chromatography analysis. The specific results are shown in Table 3.

[0133] Table 2

[0134]

[0135] Table 3

[0136]

[0137] It can be seen from the above results that the toluene conversion rate in the toluene hydrodealkylation reaction using the hydrodealkylation catalyst provided by the present invention is high, the benzene selectivity is high, the aromatic ring loss rate of toluene as a raw material is low, the aromatic hydrocarbon yield is high; and the catalyst has good stability.

[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A supported catalyst, characterized in that The catalyst comprises a composite pore molecular sieve carrier and chromium elements and rare earth elements loaded on the carrier; The pore volume of the catalyst is greater than 0.3 mL / g and the specific surface area is less than 280 m 2 / g.

2. The catalyst according to claim 1, wherein The volume ratio of micropores to mesopores of the composite molecular sieve is 2.8-8.5, preferably 3.5-6.0; and / or The mesopore diameter of the composite molecular sieve is 5-35 nm, preferably 8-18 nm; and / or The pore volume of the catalyst is 0.40-1.2 mL / g, preferably 0.65-0.95 mL / g; and / or The specific surface area of ​​the catalyst is 100-265m 2 / g, preferably 125-205m 2 / g; and / or The average pore size of the catalyst is 4.5-16 nm, preferably 6.0-12.5 nm.

3. The catalyst according to claim 1 or 2, wherein The type of the composite pore molecular sieve is selected from at least one of MCM-22 molecular sieve, mercerized molecular sieve, ZSM-5 molecular sieve, β molecular sieve, and Y molecular sieve; Preferably, it is at least one of MCM-22 molecular sieve, mercerized molecular sieve and ZSM-5 molecular sieve; More preferably, it is a mixed molecular sieve with a mass ratio of MCM-22 molecular sieve to ZSM-5 molecular sieve of 80-60:20-40.

4. The catalyst according to any one of claims 1 to 3, wherein The rare earth element is a rare earth oxide, and preferably the rare earth oxide is at least one selected from lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide and samarium oxide; More preferably, it is at least one of lanthanum oxide, cerium oxide and praseodymium oxide; More preferably, it is a mixture of lanthanum oxide, cerium oxide and praseodymium oxide; More preferably, the molar ratio of lanthanum oxide, cerium oxide and praseodymium oxide in the mixture is 0.90-0.50: 0.05-0.30: 0.05-0.

20.

5. The catalyst according to any one of claims 1 to 4, wherein The weight ratio of the composite pore molecular sieve carrier, chromium in terms of oxide and rare earth in terms of oxide in the catalyst is 1:0.03-0.10:0.05-0.15; preferably 1:0.05-0.08:0.09-0.

13.

6. The method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The method includes: (1) first loading a rare earth metal source onto an acid-treated composite pore molecular sieve carrier, performing a first drying and a first calcination to obtain a catalyst intermediate; (2) A chromium source is loaded onto the catalyst intermediate for a second time, followed by a second drying and a second calcination.

7. The preparation method according to claim 6, wherein: The acid treatment uses an acid concentration of 0.01-0.2 mol / L, preferably 0.05-0.15 mol / L; and / or The acid treatment conditions include: The temperature is 45-100°C, preferably 60-95°C; and / or The time is 4-12 hours, preferably 6-8 hours; and / or The liquid-to-solid ratio is 4.5-15, preferably 6-11; and / or The acid treatment uses an acid selected from an inorganic acid and / or an organic acid; Preferably at least one selected from oxalic acid, citric acid, acetic acid and hydrochloric acid; More preferably, it is at least one of oxalic acid, citric acid and acetic acid.

8. The preparation method according to claim 6 or 7, wherein: The chromium source is selected from at least one of chromium nitrate, chromium sulfate, chromium chloride and potassium alum, preferably at least one of chromium nitrate, chromium sulfate and chromium chloride; and / or The rare earth metal source is selected from at least one of lanthanum nitrate, cerium nitrate, praseodymium nitrate, neodymium nitrate and samarium nitrate, preferably at least one of lanthanum nitrate, cerium nitrate and praseodymium nitrate.

9. The preparation method according to any one of claims 6 to 8, wherein: The conditions of the first load include: a temperature of 50-150° C., preferably 80-120° C.; and / or a time of 4-12 hours, preferably 6-8 hours; and / or The first drying conditions include: a temperature of 70-150° C., preferably 90-120° C.; and / or a time of 5-10 h, preferably 6-9 h; and / or The first calcination conditions include: a temperature of 400-650° C., preferably 450-550° C.; and / or a time of 2-8 hours, preferably 4-6 hours; and / or The conditions of the second load include: a temperature of 50-150° C., preferably 80-120° C.; and / or a time of 6-15 h, preferably 8-12 h; and / or The second drying conditions include: a temperature of 70-150° C., preferably 90-120° C.; and / or a time of 5-10 h, preferably 6-9 h; and / or The conditions for the second calcination include: a temperature of 400-600° C., preferably 450-550° C.; and / or a time of 2-8 hours, preferably 2-6 hours.

10. Use of the catalyst according to any one of claims 1 to 5 in the preparation of benzene by hydrogenation and dealkylation of alkylbenzene, wherein the alkyl group in the alkylbenzene is preferably a C1-C5 alkyl group, and more preferably the alkylbenzene is toluene.

11. A method for preparing benzene by hydrogenating and dealkylating alkylbenzene, characterized in that: The method comprises: contacting and reacting a hydrogen raw material and an alkylbenzene raw material in the presence of the catalyst described in any one of claims 1 to 5; Preferably, the contact reaction conditions include: a temperature of 400-600°C, preferably 420-550°C; and / or a pressure of 0.1-5 MPa, preferably 0.5-3.5 MPa; and / or a mass space velocity of alkylbenzene of 1-10 h -1 , preferably 2.0-5.0h -1 ; and / or a hydrogen-to-oil ratio of 500-1500, preferably 800-1200; Preferably, the alkyl group in the alkylbenzene is a C1-C5 alkyl group, and more preferably the alkylbenzene is toluene.